Praktik signifikasi atas transformasi pelayanan referensi di Perpustakaan Universitas Indonesia - Indira Irawati (Universitas Padjadjaran, 2020)
The transformation of reference services in academic libraries in the era of information technology has a significant impact on librarians. Librarians need to address transformation properly to design the right services. The University of Indonesia (UI) library has undergone this transformation since a decade ago and continues to adapt to existing developments. Various service concepts were developed to suit users' demands, including by providing online-based services and utilizing social media to communicate with users. This study aimed to explore how reference librarians interpreted this transformation and what they should do. The research method used qualitative methods with the phenomenological method narrated descriptively. The research informants consisted of 13 librarians and seven reference librarians. Data analysis showed that librarians'significance for transforming reference services resulted in 4 important themes that were interpreted as influencing their work as reference librarians. The four themes were digital-based library services, expansion of access, policy, and promotion. This research concludes that users and librarians' practice of significance for the transformation of reference services results in the digital libraries' concept, which requires expansion of access, relevant policies, and social media optimization for service promotion. The practice of significance related to communication patterns with reference users in the digital era effectively uses email and chatting on the WhatsApp application.